Dynamic Response Analysis of Gearbox Housing Under the Variable-speed Drive - Huang Yonghui; Chu Chaomei; Tan Hui; Miao Guo (Jixie chuandong)
In order to obtain the vibration response of the automobile gearbox housing accurately,a method of obtaining the dynamic response of the gearbox housing under the variable-speed drive is proposed. The pre-transverse gearbox housing is taken as the research object,the dynamics model of the gear transmission system is built,and the dynamic loads of the bearing holes under the variable-speed drive are obtained by the multi-body dynamics analysis. On this basis,the dynamic response analysis of the gearbox housing is carried out by using the modal superposition method. The vibration displacement,velocity and acceleration response of the gearbox housing are obtained. The experimental results show that the simulation result is very close to the experimental results and the maximum error is less than 10%.